DISTRESS DAN SELF-HELP STRATEGIES PERAWAT MENGHADAPI COVID-19 BERBASIS MENTAL HEALTH WEB-TRAINING - Chlara Yunita Prabawati; Dian Istanti; Diah Priyantini; Erfan Rofiqi; Septian Galuh Winata (Jurnal Keperawatan Muhammadiyah, 2022)
Objective: to identify the relationship of distress and self-help strategies of mental health web training among nurse face the COVID-19. Methods: This article use quantitative study with simple random sampling, the questionnaire was use are the  Percieved Stress Scale 10  and Modified develop Self-strategy ScaleResults:  The moderate diagnostic, severe diagnostic and very severe diagnostic distress shown have very significant correlated with the self-help strategies use M-health web Training among nurses (B = 1,27; B = 1,21; B = 1,01, p < 0.1)Conclusion:  The moderate diagnostic, severe diagnostic and very severe diagnostic distress shown have very significant correlated with the self-help strategies M-health web Training among nurses , Need further collaboration between institutions for complete longitudinal research due to management distress among nurses